Transportation [1999 technology analysis and forecast]. - Bretz, E.A.
This article presents a transportation technology analysis and forecast for 1999. The subjects covered include automated toll collection, automobile navigation automation, high-speed electric railways, Maglev and rapid transit systems
Keywords: AD 1999.; Maglev; Automated toll collection; Automobile navigation; High-speed electric railways; Rapid transit systems; Technology analysis; Technology analysis and forecast; Transportation technology